Practical training report: Road Transport Department (RTD) / Mazuin Amir - Amir, Mazuin (University Technology MARA Sarawak, 2013)
Road Transport Department (JPJ) was established in 1937 under the Traffic Enactment 1937. The administration was then known as the Road Transport Board that works by regulating and licensing of public enterprises. With the establishment of the administration of Malaya in April 1946, the authority of the board has been taken over by the Office of the Registrar and Motor Vehicles Inspection that covers the whole of the Malaya. Before 1937, the regulation of motor car is under the four Federated Malay States of the Lower Police of Perak and Selangor, Chief Inspector of Negeri Sembilan and the 6th District Officer of Pahang. The regulation of motor car is not effective in the Unfederated Malay States such Johor, Kedah, Kelantan, Perlis dan Terengganu apart from the four states regarding the motor vehicle until the approval of the Traffic Enactment 1937. In line with the opening of the department, there is a law known as the Road Traffic Ordinance 1953 that has been approved to replace the Traffic Enactment 1937. It is very important to enforce the law especially for the commercial vehicles, so the Enforcement Division has been set up to carry out the enforcement functions.